It's getting better all the time (can't get no worse): the why, how and when of environmental entrepreneurship. (2018) - York, Jeffrey G.
In this essay, I discuss the current boundaries and potential promise of environmental entrepreneurship research. I argue that environmental entrepreneurship provides a unique lens to study how to effectively address human-induced climate change. However, for such studies to be effective, we need to understand: 1) why some individuals choose to pursue environmental entrepreneurship; 2) how organisations pursue integrated economic and ecological goals; 3) when does such action have a significant impact. I propose these three questions provide an agenda for understanding the simultaneous pursuit of economic and ecological benefits through the creation of new products, services, and markets.